Digital Didactical Designs as research framework: iPad integration in Nordic schools. (October 2017) - Jahnke, Isa; Bergström, Peter; Mårell-Olsson, Eva; Häll, Lars; Kumar, Swapna
Abstract: In this research, the design of teaching and learning with web-enabled technologies, such as iPads, in 64 one-to-one (1:1) Nordic classrooms was explored using the Digital Didactical Design (DDD) framework. DDD focuses on both teachers' activities and students' learning activities in the classroom and how web-enabled technologies are integrated into teaching, learning, and assessment. Semi-structured classroom observations were conducted to investigate how teachers apply the elements of DDD in their classroom practice, and what kinds of learning they support. The analysis resulted in three clusters: Cluster A demonstrates integration and alignment toward meaningful learning; Cluster B shows the potential for deep learning but a semi-alignment of teaching, learning, assessment, roles, and technology; and Cluster C indicates non-integration of the five elements. The findings point out that tablet integration needs the alignment of all five DDD elements to achieve meaningful learning. Pedagogy has to evolve to include new uses of the technology: it is a co-evolutionary growth of the five DDD elements together. DDD can be used by teachers for planning, self-assessment or reflective collaboration with peers and by schools to plan, document, evaluate, and rethink the interwoven pedagogy-technology relationship in tablet classrooms. Highlights: Digital Didactical Design is useful for analyzing tablet classroom practices. Classroom observations reveal meaningful, semi-integrated and shallow learning. A third of the classrooms achieve meaningful learning with iPads. DDD developed a new framework that may guide education in the digital age. Schools can use the DDD coding scheme to evaluate teaching/learning with tablets.